THE POPULATION OF FLIES IN CIKOLOTOK LANDFILL, PASAWAHAN DISTRICT, PURWAKARTA REGENCY, INDONESIA - Danang Wahansa Sugiarto; Retno Hestiningsih; Rully Rahadian (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: The flies act as mechanical vectors of disease to the digestive tract, such as cholera, typhoid, dysentery, and others. There are a lot of flies in a variety of habitats, one of the preferred habitat is on landfills. The first step to controlling flies is a preliminary survey with collecting data about the population of flies. In the Cikolotok landfill, it has never done a survey population of flies. Aims: This study aims to look the number of flies and the priority area for fly control, the most active time of flies, and species of flies in Cikolotok landfill, Pasawahan District, Purwakarta Regency, Indonesia. Methods: This study was an observational-descriptive research. The flies were observed based on the fly that caught by the flypaper trap and cone trap mounted on 3 areas, i.e. area of sorting garbage, area of stockpiling garbage and area of waste treatment. Data were analyzed by univariate method. Results: The results showed that the density of flies in Cikolotok landfill per point range between 0- 179 flies/15 minutes in every 2-hour. The area that had the highest number of flies is area of sorting garbage with 528 flies. The most active time of flies was in a span of 7:00-9:00 am. The species of flies were found are Chrysomya megacephala (52%), Musca domestica (45%) and Sarcophaga bullata (3%). Conclusion: Sorting garbage area has the highest number of flies and C. megacephala more found in landfill because of physical condition of garbage and the condition of area itself. The flies are more active in a span of 07:00-09:00 due to the condition of physical environment. Monitoring, fly control, research about fly-borne disease and relocation of cattle are needed to control the flies and the effects.